We are here with you hands in hands to facilitate your learning & don't appreciate the idea of copying or replicating solutions. Read More>>
.+ http://bit.ly/vucodes (Link for Assignments, GDBs & Online Quizzes Solution)
+ http://bit.ly/papersvu (Link for Past Papers, Solved MCQs, Short Notes & More)+ Click Here to Search (Looking For something at vustudents.ning.com?) + Click Here To Join (Our facebook study Group)
Simplifying 7y + -60 = 12y
Reorder the terms: -60 + 7y = 12y
Solving -60 + 7y = 12y
Solving for variable 'y'.
to each side of the equation.
-60 + 7y + -12y = 12y + -12y
Combine like terms: 7y + -12y = -5y -60 + -5y = 12y + -12y
Combine like terms: 12y +
-12y = 0
-60 + -5y = 0
Add '60' to each side of the equation.
-60 + 60 + -5y = 0 + 60
Combine like terms: -60 + 60 = 0
0 + -5y = 0
+ 60 -5y = 0 + 60
Combine like terms: 0 + 60 = 60
-5y = 60
Divide each side by '-5'. y = -12
Simplifying y = -12